The Intercultural Communicative Competence (ICC) Level of Paraprofessional Translators - Allvian Susanto; Barans Irawan Palangan; Afi Normawati (Surakarta English and Literature Journal, 2023)
This study investigated para-professional translators' intercultural communicative competence (ICC) level and its relation to their translations. The research design of this study is descriptive research. Twelve participants are participating in the research. The techniques of data collection employed in this study are questionnaires and tests. The results of the research show that : (1) The average ICC level of the para-professional translators is moderate level with a score of 3.0; (2) The average score of translation works from the participant with the lowest ICC level is 70; (3) the average score of translation works from the participant with the highest ICC level is 84.5; (4) the participant with the highest ICC level has a better score in the aspects of usefulness/ transfer, terminology/ style and idiomatic writing in their translation works.